Distortion of mannoimidazole supports a B2, 5 boat transition state for the family GH125 α-1, 6-mannosidase from Clostridium perfringens. Issue 34 (13th August 2019) - Males, Alexandra; Speciale, Gaetano; Williams, Spencer J.; Davies, Gideon J.
Abstract : Enzyme transition-state mimics can act as powerful inhibitors and allow structural studies that report on the conformation of the transition-state. Abstract : Enzyme transition-state mimics can act as powerful inhibitors and allow structural studies that report on the conformation of the transition-state. Here, mannoimidazole, a mimic of the transition state of mannosidase catalyzed hydrolysis of mannosides, is shown to bind in a B 2, 5 conformation on the Clostridium perfringens GH125 α-1, 6-mannosidase, providing additional evidence of a O S 2 – B 2, 5 – 1 S 5 conformational itinerary for enzymes of this family.